Efficacy of TLR7 agonistic imidazoquinoline as immunochemotherapeutic agent against P. Berghei ANKA infected rodent host. Issue 9 (1st May 2019) - Saroa, Ruchika; Kaushik, Deepender; Bagai, Upma; Kaur, Sukhbir; Salunke, Deepak B.
Graphical abstract: Abstract: Malaria is a serious disease and is one of the most alarming public health issues. Plasmodium is being resistant to various antimalarials including Chloroquine (CQ) which was the first-line therapy for malaria treatment. WHO recommended several combination therapies but declining efficacy was reported to many of these therapies. Despite a great amount of research, efficient malaria vaccine still seems to be a distant dream. Immunochemotherapy could be an alternate strategy to deal with malaria. Based on the differential activity of various cytokines in the pathogenesis of and protection against malaria, the efficacy of highly active TLR7 agonistic imidazoquinoline (BBIQ) in combination with a suboptimal dose of CQ against P. berghei ANKA (PbA) in vivo was investigated. In mice treated with CQ alone, parasite appeared on Day 17 and all mice of this group died by Day 21. Whereas, mice treated with BBIQ along with CQ exhibited no appearance of parasite till Day 23. Frequencies of T cells (CD3 +, CD4 + and CD8 + ) and T regulatory cells (CD4 +, CD25 + and FoxP3 + ) were found to be lower in brain of BBIQ + CQ treated mice as compared to BBIQ alone and CQ alone treated mice on Day 10. Inhibition of infiltration of inflammatory T cells and activation of T helper and T cytotoxic cells against the parasite was observed in the mice treated with this combination therapy. Serum levels of IFN-γ and IL-12 were found to be higher on same day in mice treated with BBIQ + CQ which revealed the generation of strong Th1 immune response in mice against the infection. Overall, TLR7 agonist acted as an efficient partner when combined with potent antimalarial drug.